Optimization of aicraft trajectories in North Atlantic oceanic airspace - Rodionova, Olga; Sbihi, Mohammed; Delahaye, Daniel; Mongeau, Marcel (HAL CCSD, 2012)
International audience Air traffic control in non-radar oceanic airspace has always been relatively limited. Current American and European projects aim at transiting from ground-based systems to satellite-based systems. New technologies will allow to reduce significantly the present aircraft separation standards. As a consequence, the aircraft crossing the North Atlantic will be able to follow better routes, which will improve the air traffic situation by decreasing of flight durations and congestion in pre-oceanic continental airspace. In this paper an optimization model is introduced and a simple methodology to solve this problem is proposed that yields encouraging preliminary results.